Impact of Policies and Supervision on Health Worker Satisfaction at Bahteramas Hospital - Risky, Sartini; Ardiansyah, Ririn Teguh; Firmansyah, Firmansyah (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Providing quality services is inseparable from human resources that produce good performance and achievement. One of the factors related to the performance or work performance of nurses is the low satisfaction of a person with their job. Currently, it is known that the main problem that often arises in human resource management is how to find the best way to achieve employee job satisfaction. Employee complaints about supervision that is very rarely carried out. This makes employees feel that their work is not supervised. This study aims to study the relationship between organizational policies and supervision with the satisfaction of health workers in the BLUD inpatient room of Bahteramas Hospital. This research is a quantitative study with a cross-sectional study approach, and research was conducted on February 2023 in the inpatient room of Bahteramas Hospital. The population in this study were all health workers who worked in the BLUD inpatient room of Bahteramas Hospital, totaling 213 people with a sample of 139 respondents. Data analysis was carried out computerized using the SPSS version 25.0 program, to analyze the relationship between the independent and dependent variables together, the Logistic Regression test was used. Results of the analysis show that all variables that have a probability value (p-value) <0.05 include organizational policies (p=0.141), and supervision (p=0.032). These results indicate that the supervision variable has a significant relationship. Meanwhile, the organizational policy variable does not have a significant relationship with the satisfaction of health workers in the BLUD Inpatient Room of Bahteramas Hospital. There is a moderate relationship between organizational policies and supervision with the satisfaction of health workers in the BLUD Inpatient Room of Bahteramas Hospital.